Therapeutic strategies against COVID-19 - Esposito, Susanna; Gnocchi, Margherita; Gagliardi, Martina; Affanni, Paola; Veronesi, Licia; Colucci, Maria Eugenia; Neglia, Cosimo; Argentiero, Alberto; Principi, Nicola (Acta Biomedica Atenei Parmensis, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a novel coronavirus that mainly affects the upper and lower respiratory tract and is responsible for extremely different degrees of disease, ranging from flu-like symptoms to atypical pneumonia that may evolve to acute respiratory distress syndrome and, ultimately, death. No specific therapy for SARS-CoV-2 has yet been identified, but since the beginning of the outbreak, several pre-existing therapeutics have been reconsidered for the treatment of infected patients. The aim of this article is to discuss current therapeutics against SARS-CoV-2. A literature review was performed using PubMed, collecting data from English-language articles published until June 20th, 2020. Literature analysis showed that with the acquisition of more in-depth knowledge on the characteristics of SARS-CoV-2 and the pathogenesis of the different clinical manifestations, a more rationale use of available drugs has become possible. However, the road to defining which drugs are effective and which schedules of administration must be used to maximize efficacy and minimize adverse events is still very long. To date, it is only clear that no drug can alone cope with all the problems posed by SARS-CoV-2 infection and effective antivirals and inflammatory drugs must be given together to reduce COVID-19 clinical manifestations. Moreover, choice of therapy must always be tailored on clinical manifestations and, when they occur, drugs able to fight coagulopathy and venous thromboembolism that may contribute to respiratory deterioration must be prescribed.